The USADA’s supposed orthodox approach to anti-doping: a power strategy and a threat to trust - Ohl, Fabien (Frontiers in Sports and Active Living, 2025)
This article analyses the roots of the significant tensions between USADA and WADA over the revelations that 23 Chinese swimmers were found to have a banned substance in 2021. USADA described the revelation as a scandal and criticised WADA for a lax policy that failed to fulfil its role. USADA's position, which can be described as a way of overplaying orthodoxy, is seen as an attempt to control the "doxa" of sport and thus gain power within the Olympic movement. This vehement demand for a change in WADA policy can be seen as one of the expressions of the imperialist stance of the United States, which favours power relations over deliberation and multilateralism and risks undermining confidence in anti-doping.